Forensic Monitoring Project Report: Bugojno Exhumations of Federal Commission on Missing Persons Croat Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Hudson, Page Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Kennedy, Brenda On 26 April 1998, the Federal Commission on Missing Persons Croat Side exhumed the remains of seven individuals from two Catholic cemeteries near the town of Bugojno. Three bodies were recovered from a cemetary in Sultanovići and four bodies from Vučipolje. The recovered bodies were all male Bosnian Croats believed to be killed on 31 October 1993 while trying to escape fighting in the region. Place of Exhumation: Bugojno Exhumation Site: Sultanovići, Vučipolje Date of Exhumation: 26 April 1998 Minimum Number of Exhumed Individuals: 007